PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTU MEDIA TANGRAM TERHADAP HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR - Agtri Niranty; Iyan Irdiyansyah; Resyi A Gani (STKIP Subang, 2023)
The Influence of Application of Problem Based Learning Model Assisted by Tangram Media on Mathematics Learning Outcomes of Flat Shape Material. This study uses a quasi-experimental approach at Pabuaran State Elementary School 04. Research Subjects are fourth grade students of Pabuaran State Elementary School 04. The study was conducted in the even semester of the 2021/2022 academic year. The results of the study indicate that there is an effect of applying the Problem Based Learning model with the aid of tangram media on the learning outcomes of mathematics in the flat wake material. this can be seen from the N-gain value in the experimental class which is 65.23 while the control class is 54.25. The completeness of learning outcomes in the experimental class is 73.07% and the control class is 50%. And the results of hypothesis testing that the null hypothesis (Ho) is rejected and Ha is accepted because tcount (3.42) > ttable (2.01063). Thus, it can be concluded that the research has a positive and significant influence on the application of the Problem Based Learning model with the aid of tangram media on the learning outcomes of flat-shaped materials.